Large increase in CH4 emission following conversion of coastal marsh to aquaculture ponds caused by changing gas transport pathways. (15th August 2022) - Yang, Ping; Lai, Derrick Y.F.; Yang, Hong; Lin, Yongxin; Tong, Chuan; Hong, Yan; Tian, Yalan; Tang, Chen; Tang, Kam W.
Highlights: Converting coastal marsh to aquaculture ponds lowered sediment CH4 production. Main CH4 emission pathway shifted from plant-mediated transport to ebullition. Subsequent CH4 emission was more than 10 times higher in aquaculture ponds. Temperature and carbon substrate supply affected seasonal variations in CH4 flux. Abstract: Methane emissions from aquatic ecosystems play an important role in global carbon cycle and climate change. Reclamation of coastal wetlands for aquaculture use has been shown to have opposite effects on sediment CH4 production potential and CH4 emission flux, but the underlying mechanism remained unclear. In this study, we compared sediment properties, CH4 production potential, emission flux, and CH4 transport pathways between a brackish marsh and the nearby reclaimed aquaculture ponds in the Min River Estuary in southeastern China. Despite that the sediment CH4 production potential in the ponds was significantly lower than the marsh, CH4 emission flux in the ponds (17.4 ± 2.7 mg m −2 h −1 ) was 11.9 times higher than the marsh (1.3 ± 0.2 mg m −2 h −1 ). Plant-mediated transport accounted for 75% of the total CH4 emission in the marsh, whereas ebullition accounted for 95% of the total CH4 emission in the ponds. CH4 emission fluxes in both habitat types were highest in the summer. These results suggest that the increase in CH4 emission following the conversion of brackish marsh to aquaculture ponds was not caused by increased sediment CH4 production, but rather by eliminating rhizospheric oxidation and shifting the major transport pathway to ebullition, allowing sediment CH4 to bypass oxidative loss. This study improves our understanding of the impacts of modification of coastal wetlands on greenhouse gas dynamics. Graphical abstract: Image, graphical abstract